SEJARAH PERKEMBANGAN TIMOR LESTE PASCA REFERENDUM 2002 -2017 - Giri Handito Mahatera; Bedriati Ibrahim; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Timor Leste is a new country in the world and is a former province in Indonesia. In 1997 held a referendum and succeeded in becoming an independent country in 2002. Various types of conflicts occurred before and after East Timor broke away from Indonesia. As a new country, the development of Timor Leste needs to be observed both in terms of its social, economic and political conditions, as well as cooperation carried out with other countries, especially Indonesia as the closest neighboring country to support the continued establishment of Timor Leste. By conducting research using the literature study method, this study discovers what developments have occurred in Timor Leste after the referendum.Key Words: Development, Timor Leste, Referendum.